Gender violence and sexism in Italy. Norms, control and sexuality - Peroni, Caterina (La camera blu. Rivista di studi di genere, 2014)
Gender-based violence and prostitution are social facts that historically in the way they are represented and socially constructed processes produce ethnicization, essentialism, culturalization of female bodies and deviant than the heterosexual norm. In this paper we compare two different waves discourse, on the one hand that securitarian (2007-2009) that has seen violence and prostitution both devices to agitate social alarms, justify repressive measures, reproduce rhetorical securitarian and at the same time reaffirm social gender roles essentialized, on the other the next (2010-2012), in which violence against women, in part thanks to the power of word of Italian feminists, yes is given in the home, but how did outstanding and without questioning the state of relations gender in our society, while the sex scandals linked to Berlusconi and the spread of a discursive order distorts neo-moralistic terms such as prostitution, violence, selfdetermination and freedom. These two cases are epiphenomena of a trend that sees women's bodies and their sexuality object of devices and discursive orders useful to reaffirm the heterosexual norm, asymmetrical gender relations, and more generally a given social order based on the control of body.